The afterlife of industrial work: Urban-to-rural labour transitions from the factory to the informal economy - Alessandra Mezzadri; Kaustav Banerjee (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
The COVID-19 pandemic has escalated processes of labour transition from industrial work to the informal economy, which have always characterized the life of the working poor. Exploring urban-to-rural labour transitions through a feminist political economy lens and adopting a life-cycle approach to labour and social reproduction, this paper analyses the post-industrial livelihoods and experiences of former Indian garment workers leaving the National Capital Region and moving back to Bihar. Emphasis is placed on workers' reasons for leaving the industry and their current employment and reproductive strategies. Findings are based on a sample of 50 former workers, identified in urban industrial hamlets and traced back to their place of origin. Respondents' experiences are analysed based on semi-quantitative questionnaires and life histories. Findings reveal that upon leaving the factory, workers find alternative informal employment through caste or social networks while using land as safety net. Farming and informal work are not alternative but rather complementary income and work strategies. By adopting a life-cycle approach to studying labour transitions across formal and informal employment domains, this analysis contributes to policy debates on decent work.
Keywords: B54; J46; P16; R23; 330; feminist political economy; social reproduction; informal economy; urban-to-rural labour transitions; post-industrial livelihoods; life-cycle approach